Dynamics of the radix expansion map - Ben Goertzel; Harold Bowman; Richard Baker (International Journal of Mathematics and Mathematical Sciences)
The chaotic dynamics of the map ϕ(x)=(βx+α)(mod1) are studied using Parry's β-expansion. It is shown that for 1<β<2, a≥0, the number of periodic points of period n is 0(βn).